2021
DOI: 10.3390/pharmaceutics13040547
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy of Novel Oncolytic Adenovirus with Anti-PD1 Resulted in Enhanced Anti-Cancer Effect in Syngeneic Immunocompetent Melanoma Mouse Model

Abstract: Malignant melanoma, an aggressive form of skin cancer, has a low five-year survival rate in patients with advanced disease. Immunotherapy represents a promising approach to improve survival rates among patients at advanced stage. Herein, the aim of the study was to design and produce, by using engineering tools, a novel oncolytic adenovirus AdV-D24- inducible co-stimulator ligand (ICOSL)-CD40L expressing potent co-stimulatory molecules enhancing clinical efficacy through the modulation of anti-cancer immune re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 87 publications
1
13
0
2
Order By: Relevance
“…The vector was generated and amplified using standard adenovirus preparation techniques [ 37 , 38 ]. Briefly, the Ad5 WT virus was used as a backbone for the construct (Genbank #AY339865), and the following genetic modifications were made: (i) deletion of 24 bp in the E1A conserved region, (ii) insertion of the inducible costimulatory ligand (ICOSL) [ 39 , 40 ] was placed under the exogenous promoter in the E3 region. Additionally, the fiber knob was modified (AdV5/3 chimeric).…”
Section: Methodsmentioning
confidence: 99%
“…The vector was generated and amplified using standard adenovirus preparation techniques [ 37 , 38 ]. Briefly, the Ad5 WT virus was used as a backbone for the construct (Genbank #AY339865), and the following genetic modifications were made: (i) deletion of 24 bp in the E1A conserved region, (ii) insertion of the inducible costimulatory ligand (ICOSL) [ 39 , 40 ] was placed under the exogenous promoter in the E3 region. Additionally, the fiber knob was modified (AdV5/3 chimeric).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the levels of IFN-g, IL-2, and TNF-a in the pleural fluid increased after viral administration in 8 patients out of 11, thus suggesting a direct correlation with the induction of meaningful antitumor immunity (109). Oncolytic virotherapy is a rapidly growing field of immunotherapy that has been studied across a broad spectrum of malignancies (103,(110)(111)(112)(113). Mesothelioma is a good candidate for studying oncolyses, given its frequently localized pattern of growth and location.…”
Section: Oncolytic Virusesmentioning
confidence: 99%
“…The immunosuppressive TME favoring melanoma ICI resistance can be taken advantage of as a target for viral attack; dysfunctional immune signaling allows genetically engineered non-pathogenic viruses to selectively target cancer cells and consequently replicate in them to a greater extent than in normal cells ( 28 , 31 ). OVTs have been associated with activation of T and NK cells, release of immunogenicity stimulating agents, release of tumor-specific antigens for APC uptake, type I IFN signaling, and major histocompatibility complex (MHC) upregulation ( 32 , 33 ). The overall response rate to T-VEC monotherapy is only around 25% ( 34 ), but the true promise of OVTs arguably lies in their immunomodulatory properties.…”
Section: Current Immunotherapies For Melanomamentioning
confidence: 99%
“…Tumor adenovirus OVT injection drastically alters the immune landscape with increased NK, T cell and APC migration occurring. Interestingly, initial trials observed that OVTs were associated with an increase of PD-1 and PD-L1 expression ( 32 ). In response to these findings, recent reports reveal PD-L1 expression is an adaptive mechanism used by melanoma to generate OVT resistance ( 33 , 35 ).…”
Section: Current Immunotherapies For Melanomamentioning
confidence: 99%